2003
DOI: 10.5194/acp-3-521-2003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of aerosol properties over Europe derived from satellite observations and comparison with model calculations

Abstract: Abstract. Aerosol optical depths (AOD) and Angström coefficients over Europe were retrieved using data from the ATSR-2 radiometer on board the ESA satellite ERS-2, for August 1997. Taking advantage of the nadir and forward view of the ATSR-2, the dual view algorithm was used over land to eliminate the influence of the surface reflection. Over sea the AOD was retrieved using only the forward observations. Retrieved aerosol optical properties are in good agreement with those from ground-based sunphotometers. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Several authors identify a pivot point around 2006(Kang et al, 2016Zhang et al, 2017;Zhao et al, 2017) after which the AOD fluctuates before the decrease sets in from 2011 . Using a different analysis method, Zhang et al (2017) suggest a decrease starting from about 2006-2008.…”
Section: Seasonal Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors identify a pivot point around 2006(Kang et al, 2016Zhang et al, 2017;Zhao et al, 2017) after which the AOD fluctuates before the decrease sets in from 2011 . Using a different analysis method, Zhang et al (2017) suggest a decrease starting from about 2006-2008.…”
Section: Seasonal Variationmentioning
confidence: 99%
“…However, that approach may fail over very bright surfaces such as snow, ice or some desert areas. ATSR AOD data retrieved using the ADV algorithm have been successfully applied in many studies (e.g., Veefkind et al, 1998Veefkind et al, , 1999Veefkind et al, , 2000Robles-Gonzalez et al, 2000, 2006Schmid et al, 2003;Sundström et al, 2012;Holzer-Popp et al, 2013;Virtanen et al, 2014;Rodriguez et al, 2015;Sogacheva et al, 2015Sogacheva et al, , 2017Popp et al, 2016). By combining the ATSR-2 and AATSR data sets, a unique time series of AOD over land, from June 1995 to April 2012, offers the opportunity to analyze the temporal variation of the AOD and possibly detect trends.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between satellite-derived and simulated AOT from Chemistry-Transport Models have also been made (e.g. Robles González et al, 2003;Jeuken et al, 2001;Hodzic et al, 2004;Hodzic et al, 2006). Satellite measurements have the advantage that they provide horizontal information.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation mode particles also play an important role in governing the optical properties inside the continental boundary layer. Robles González et al (2003) showed that large aerosol optical depth over continental Central Europe results from a high particle load in the accumulation mode. One reason is the hygroscopicity of continental and urban aerosol in the accumulation mode size range (Kandler and Schütz, 2007) and the resulting effect on the visibility with growing particles at higher relative humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Six EUSAAR supersites were selected for the present analysis to provide continuous measurements of atmospheric properties over Europe in May 2008. Atmospheric conditions govern the lifecycle of aerosol microphysical phenomena by uptake of primary particles and aerosol precursors, providing favourable conditions for new particle formation and transformation processes during transport, and removal of particulate matter from the atmosphere (Raes et al, 2000). Several long term studies investigated the impact of meteorological conditions and different air mass transport paths on local aerosol properties at ground based measurement sites (e.g., Birmili et al, 2001;Tunved et al, 2005).…”
Section: Introductionmentioning
confidence: 99%